If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -20 + 7 = 12 + 6x + 3 Reorder the terms: -20 + 7 + 10x = 12 + 6x + 3 Combine like terms: -20 + 7 = -13 -13 + 10x = 12 + 6x + 3 Reorder the terms: -13 + 10x = 12 + 3 + 6x Combine like terms: 12 + 3 = 15 -13 + 10x = 15 + 6x Solving -13 + 10x = 15 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -13 + 10x + -6x = 15 + 6x + -6x Combine like terms: 10x + -6x = 4x -13 + 4x = 15 + 6x + -6x Combine like terms: 6x + -6x = 0 -13 + 4x = 15 + 0 -13 + 4x = 15 Add '13' to each side of the equation. -13 + 13 + 4x = 15 + 13 Combine like terms: -13 + 13 = 0 0 + 4x = 15 + 13 4x = 15 + 13 Combine like terms: 15 + 13 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| -5.6+8a=7a+7.6 | | -8-(-16+10)=12 | | 7x(1-4x)+5(1+2x)= | | (x^2+6x+5)+(x^2+6x+5)= | | 6x-4=16+2x | | 3/2x-y=17 | | 4m-4=rm | | 2x-6=3x+1-x-6 | | x-3/2y=13 | | -13=8m+5m | | X+(x-1)+(x+1)=90 | | 2v+3=19 | | 3(-4x)=-2(6x-9) | | 3(y-4)-4=2y+6.9 | | (-.8)(1/5)=x | | 8y=11y+3 | | w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 | | 69=3(4x-1) | | 4x-1+2x-1=5y |